Hemophagocytic Lymphohistiocytosis in a PICU of a Developing Economy: Clinical Profile, Intensive Care Needs, Outcome, and Predictors of Mortality. Issue 1 (8th October 2020) - Parajuli, Biraj; Angurana, Suresh Kumar; Awasthi, Puspraj; Nallasamy, Karthi; Baranwal, Arun; Bansal, Arun; Bansal, Deepak; Rawat, Amit; Varma, Neelam; Jayashree, Muralidharan
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To describe the clinical profile, intensive care needs, outcome, and predictors of mortality in critically ill children with hemophagocytic lymphohistiocytosis. Design: Retrospective case series. Setting: PICU of a tertiary care teaching hospital in North India. Patients: Children 2 months to 12 years old with the diagnosis of hemophagocytic lymphohistiocytosis admitted to PICU from January 2012 to April 2019 (7¼ yr). INTERVENTIONS: None. Measurements and Main Results: Sixty-two children with hemophagocytic lymphohistiocytosis (60 secondary and two primary) were enrolled. The median (interquartile range) age of the study group was 82 months (50.5–124 mo). The median (interquartile range) Pediatric Risk of Mortality III score was 16 (10–23). Majority of hemophagocytic lymphohistiocytosis was infection-associated ( n = 51; 82.3%). Among these, scrub typhus accounted for 29% of cases ( n = 18), dengue 17.7% ( n = 11), bacterial sepsis 14.5% ( n = 9), enteric fever 6.5% ( n = 4), and other infections 14.5% ( n = 9). Systemic-onset juvenile idiopathic arthritis accounted for 9.7% of cases ( n = 6) and malignancy for 4.8% patients ( n = 3). Majority of cases were treated with steroids (77.4%) and IV immunoglobulin (25.8%). Various complications noted were shock (71%), acute kidney injury (66.1%), acute respiratory distress syndrome (41.9%), disseminated intravascular coagulation (54.8%), CNS dysfunction (54.8%), multiple organ dysfunction syndrome (82.3%), and healthcare-associated infections (14.5%). Intensive care needs for primary illness and/or hemophagocytic lymphohistiocytosis included mechanical ventilation (74.2%); packed RBC (72.3%), fresh frozen plasma (40.3%), and platelet (48.4%) transfusion; vasoactive drugs (71%); and renal replacement therapy (24.2%). The median duration of PICU stay was 5 days (2.5–9.5 d) and mortality was 59.7% ( n = 37). On univariate analysis, nonsurvivors had higher Pediatric Risk of Mortality III score; higher proportion of shock, acute kidney injury, acute respiratory distress syndrome, disseminated intravascular coagulation, and multiple organ dysfunction syndrome; the need for blood and blood components, mechanical ventilation, vasoactive drugs, and renal replacement therapy; higher Vasoactive-Inotropic Score; and prolonged duration of mechanical ventilation compared with survivors. Conclusions: Hemophagocytic lymphohistiocytosis in PICU is commonly secondary to tropical infections and associated with high mortality. Higher severity of illness; shock and multiple organ dysfunction syndrome; need for blood and blood products, mechanical ventilation, vasoactive drugs, and renal replacement therapy; higher Vasoactive-Inotropic Score; and prolonged mechanical ventilation predicted death. Treatment of underlying infection and a less intense immunosuppressive therapy (steroids ± IV immunoglobulin) are suggested options. A high index of suspicion for complicating hemophagocytic lymphohistiocytosis is required in children with prolonged fever, cytopenias, organomegaly, and organ dysfunction not responding to conventional treatment.